Evaluation of oral hygiene Knowledge and Practices among patients visiting a Public Dental Institute - Naveed Irfan; Agha Taymoor Ali; Suneel Kumar Punjabi; Mowaffaq Abdullmomen Al Absi; Talha Asad Khan; Arsalan Ahmed (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Knowledge regarding oral hygiene and routine practices of maintaining that hygiene contributes to good oral and overall health of a person. The objective of the study was to evaluate the oral hygiene perception and practices among patients belonging to rural and urban areas visiting a public dental institute. METHODOLOGY: A descriptive cross-sectional study was conducted at the dental outpatient department (OPD) of the Institute of Dentistry Liaquat University Jamshoro Sindh from June-December 2019. All patients who reported the dental OPD during the duration of the study belonging to either gender and age 18-70 years were included in the study. While those who reported in emergency with painful conditions and chronic diseases like diabetes mellitus, hypertension, etc., were excluded. A written questionnaire was used to collect participant’s information including socio-demographic details and information related to oral hygiene perceptions and practices. Data was analyzed by SPSS version 24.0. RESULTS: The mean age of participants was 28.94±9.84 years, with an age range of 19-58 years. There was a statistically significant difference (p<0.05) between female and male participants regarding knowledge and perception of the role of oral cleaning in decay prevention, different methods of preventing dental problems, and the role of remnants of sweet food in damaging teeth. While statistically significant difference (p<0.05) in the type of toothbrush used, brushing technique, and frequency of changing toothbrush was demonstrated between participants belonging to rural and urban regions. CONCLUSION: Knowledge and routine practices regarding oral hygiene are much lower in residents of the rural region compared with the urban region.